Kauny Quantum Memory Method to Increase the Ability of Memorizing Qur’an in Early Childhood - Safiruddin Al Baqi; Conny Alif Asterisk (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Memorizing Al-Qur'an has priority for Muslims because it contains a guide of live. Memorizing Al-Qur'an in early childhood is important to direct children's behavior. The purpose of this study was to know the application and impact of Kauny Quantum Memory on early childhood. This study used qualitative method. Data collection techniques were interviews, observation, and documentation. The subjects of this study were 7 participants (5 students and 2 parents) at TPA Darunnajah Jurug Sooko Ponorogo, East Java. Data was analyzed by reducing data, presenting data, and presenting conclusions. The results showed that Kauny Quantum Memory used visualization and baby reading techniques, the memorization starts from short letters and was repeated, which made it easier for students to memorize. Students had good memorization skills in memorizing Al-Qur'an, they can find out the meaning of letters by symbolizing in movements, and feel comfortable when memorizing because it was implementing in relaxed atmosphere.